Information Technology Governance Analysis Using COBIT 2019 Framework at Bank Mandiri Girian Bitung Branch - Wulyatiningsih, Toetik; Mokodaser, Wilsen Grivin; Mambu, Joe Yuan (International Journal of Engineering, Science and Information Technology, 2024)
The advancement of information technology (IT) has become essential for organizations, including Bank Mandiri, where it underpins critical business functions. This study examines the implementation of IT governance at Bank Mandiri’s Girian branch using the COBIT 2019 framework, a comprehensive tool for managing IT processes effectively. Through a qualitative case study approach and interviews with key stakeholders, the study analyzes 40 IT processes across 11 design factors, with each factor scored between 75 and 100 to prioritize their importance. High-priority processes, such as Managed Solutions Identification and Build (BAI03), Managed Requirements Definition (BAI02), Managed IT Changes (BAI06), and Managed Projects (BAI11), are identified as critical to operational stability, customer satisfaction, and strategic alignment. These objectives play a fundamental role in resource allocation, supporting seamless IT operations and enhancing customer service. Processes with lower scores are deprioritized, allowing strategic focus on high-impact areas. This prioritization framework helps ensure efficient resource use, aligns IT governance with organizational goals, and reinforces the branch’s commitment to achieving reliable, customer-focused IT management. The study underscores the indispensable role of IT in supporting Bank Mandiri’s operations, where any IT disruption could significantly impact business continuity and customer satisfaction.